Frontline Science: Structural insights into Resolvin D4 actions and further metabolites via a new total organic synthesis and validation. Issue 6 (29th January 2018) - Winkler, Jeremy W; Libreros, Stephania; De La Rosa, Xavier; Sansbury, Brian E; Norris, Paul C; Chiang, Nan; Fichtner, David; Keyes, Gregory S; Wourms, Nicholas; Spite, Matthew; Serhan, Charles N
Abstract: Local production and downstream metabolism of specialized proresolving lipid mediators (SPMs) are pivotal in regulating their biological actions during resolution of inflammation. Resolvin D4 (RvD4: 4 S, 5 R, 17 S -trihydroxydocosa-6 E, 8 E, 10 Z, 13 Z, 15 E, 19 Z hexaenoic acid) is one of the more recently elucidated SPMs with complete stereochemistry biosynthesized from docosahexaenoic acid. Here, we report a new multimilligram commercial synthesis that afforded enough material for matching, validation, and further evaluation of RvD4 functions. Using LC-MS-MS profiling, RvD4 was identified at bioactive amounts in human (1 pg/mL) and mouse bone marrow (12 pg/femur and tibia). In mouse bone marrow, ischemia increased the formation of RvD4 > 37-fold (455 pg/femur and tibia). Two separate mouse ischemic injury models were used, where RvD4 reduced second organ reperfusion lung injury > 50%, demonstrating organ protection. Structure–function relationships of RvD4 demonstrated > 40% increase in neutrophil and monocyte phagocytic function in human whole blood in comparison with 2 separate trans-containing double bond isomers that were inactive. These 2 isomers were prepared by organic synthesis: 4 S, 5 R, 17 S -trihydroxydocosa-6 E, 8 E, 10 E, 13 Z, 15 E, 19 Z -hexaenoic acid (10-trans-RvD4), a natural isomer, and 4 S, 5 R, 17 S -trihydroxydocosa-6 E, 8 E, 10 E, 13 E, 15 E, 19 Z -hexaenoic acid (10, 13-trans-RvD4), a rogue isomer. Compared to leukotriene B4, D-series resolvins (RvD1, RvD2, RvD3, RvD4, or RvD5) did not stimulate human neutrophil chemotaxis monitored via real-time microfluidics chambers. A novel 17-oxo-containing-RvD4 product of eicosanoid oxidoreductase was identified with human bone marrow cells. Comparison of 17-oxo-RvD4 to RvD4 demonstrated that with human leukocytes 17-oxo-RvD4 was inactive. Together, these provide commercial-scale synthesis that permitted a second independent validation of RvD4 complete stereochemical structure as well as evidence for RvD4 regulation in tissues and its stereoselective phagocyte responses. Abstract : Resolvin D4 commercial-scale total organic synthesis elucidates new functions.